O caso Rousseau: aspectos da condenação de Rousseau em Genebra - Tomaz, Loyana Christian de Lima (2014)
It is, in this dissertation to analyze the process that ordered the arrest of Jean-Jacques Rousseau in Geneva and censorship of his works Social Contract and Emile (1762). How to thread the discussions presented here are taken as the main theoretical Letters Written from the field and Letters Written on the Mount works fundamentals. The analysis seeks to discover if Rousseau - nomenclature given to his condemnation - process is not restricted to the investigation of possible procedural irregularities, but requires examination of the entire social and political context at that time lived and pinpoint the ideas actually arranged in the works Social Contract and Emile, which led to the conviction and the order to destroy them, claiming they were reckless, wicked and scandalous. With this work, we intend not only to understand the procedure for condemnation of Rousseau, its legal, legal and religious grounds, but also check if the conviction changed the political and religious thought of Rousseau.